Utilization of Spent Arabica Coffee Grounds as Raw Material for Activated Charcoal in Liquid Bath Soap Formulation - Maysarah, Hilda; Desiyana, Lydia Septa; Nurzuhra, Siti; Illian, Didi Nurhadi (Pharmaceutical Sciences and Research, 2023)
Arabica coffee (Coffea arabica) is one of the most popular coffees among Acehnese, an ethnic group from Aceh, Indonesia. The amount of coffee consumed is directly proportional to the amount of coffee waste produced. Spent coffee grounds are the residue obtained during the brewing process. Spent coffee grounds can be utilized by converting them into active charcoal adsorbents. This study aimed to produce activated charcoal from spent arabica coffee grounds (SACG), to utilize it as an active ingredient in the liquid bath soap formulations, and to determine the best formula. The characterization of activated charcoal was conducted and compared to the Indonesian National Standard (SNI). The liquid bath soap contains activated charcoal from SACG was divided into five formulas with various concentrations of cocamidopropyl betaine (CAPB) and sodium lauryl sulphate (SLS) surfactants. Furthermore, the evaluation of liquid bath soap formula was performed. The characterization results showed that activated charcoal produced from SACG met the SNI requirements with a yield of 86.3%, volatile substance content of 10.67%, water content of 5.67%, ash content of 1.7%, pure carbon content of 81.96%, and iodium absorption of 1522.8 mg/g. The evaluation results revealed that liquid bath soap formula with activated charcoal from SACG containing a combination of 5% CAPB and 5% SLS (F5) was the best formula that met the requirements. SACG can be used as an excellent raw material for activated charcoal in liquid bath soap formulations.